Corporate Governance Structure and Firm Performance: Evidence from Consumer Product Firms in Malaysia - Albeera, Alaa A. E. (2009)
The main objective of this study is to examine the relationship between corporate governance structures and firm performance of consumer product firms listed on the Bursa Malaysia. Data were gathered from 51 companies in the financial year 2007. Five variables of corporate governance structures which are board size, board composition, audit committee size, CEO duality and CEO tenure were used in this study. Two measures of firm performance are considered which are return on assets (ROA) and operating cash flow (OCF). Regression analysis was used to examine the relationship between corporate governance and firm performance. The result indicates that audit committee size was positively related to ROA, while the proportion of independent directors is negatively related to ROA. The relationship with OCF indicates that board size and audit committee size are positively related. The results show that the most influence variable of corporate governance structure on firm performance is audit committee size.